Rapid response to monotherapy with MEK inhibitor trametinib for a lung adenocarcinoma patient harboring primary SDN1-BRAF fusion: A case report and literature review - Yu, Yang; Yu, Min; Li, Yanying; Zhou, Xiaojuan; Tian, Tian; Du, Yijia; Tu, Zegui; Huang, Meijuan (Frontiers in Oncology, 2022)
BRAF gene has become an oncogenic driver and a potential drug target in a wide variety of malignancies. BRAF fusion, a subtype of BRAF alteration, occurs at a very low frequency. Here, we report the first case of a heavily pre-treated advanced lung adenocarcinoma patient with de novo SND1-BRAF fusion showed partial response to trametinib. A review of the literature on targeting BRAF fusions is provided.